Withdrawal of hormone therapy and increased risk of cardiovascular disease. (3rd May 2016) - Pines, A.
Abstract: Many menopause specialists follow the principle of prescribing postmenopausal hormone therapy (HT) for the shortest duration needed, in order to decrease the risk of some related serious adverse effects, such as breast cancer. Based on several large studies, it seems, however, that withdrawal of HT may be associated with immediate, though small increased risk of coronary heart disease and stroke. Cessation of HT correlates with increased risk of fractures as well. This information should be relayed to hormone users while discussing the continuation of HT with their health-care provider, but, since the potential cardiovascular harm is actually very small, it should not deter symptomatic women from using HT when needed.